Understanding the Impact of Curing Duration on Characteristics of Durian Extract-Based Solid Soap - Imani, Nadya Alfa Cahaya; Pribadi, Meidwiarta Cahya; Irsyada, Muhamad Zakky; Kusumaningrum, Maharani; Asri, Sarwi; Ardhiansyah, Hanif (Indonesian Journal of Chemical Research, 2025)
This study aims to understand the effect of curing duration on the characteristics of durian extract-based solid soap. Durian extract-based soap has unique properties that can be affected by the curing process, namely the duration of drying and maturation of the soap after manufacture. In this study, soap was produced using durian extract as the main ingredient, with curing time variations ranging from 2 weeks to 6 weeks. During the curing process, the water content in the soap decreased, and the saponification reaction between alkali and free fatty acids from durian extract took place further. The characteristics of the soap analyzed included hardness, pH, free fatty acid content, and foam durability and quality. The results showed that the soap became more challenging as the curing time increased, with a more stable pH and lower free fatty acid content. In addition, the durability of the soap increased, and the foam quality became more optimal. Longer curing durations were also associated with increased stability and safety of the resulting soap. This study provides new insights into the development of durian extract-based soap. It can be used as a reference to improve the quality of natural soap products through proper curing process management.